2008
DOI: 10.1258/la.2007.007033
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral optical nerve hypoplasia in a Beagle dog

Abstract: SummaryUnilateral (left eye) optic nerve hypoplasia was detected in a six-month-old male Beagle dog. Vision testing indicated that the left eye had poor vision and testing the pupillary light reflex showed the left eye to have an absence of the afferent pathway of the reflex but it had a normal efferent pathway. Ophthalmoscopy revealed a small-sized optic disc, winding retinal artery and dilated retinal vasculature in the left globe. Electroretinography showed no abnormal findings even in the left globe. Histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Garcia da Silva et al identified also this abnormality in a group of dogs with a median age of diagnosis of 16.1 months, being mainly bilateral in presentation 61 . Negishi et al also reported a case of optic nerve hypoplasia in a 6‐month‐old Beagle 62 …”
Section: Discussionmentioning
confidence: 86%
“…Garcia da Silva et al identified also this abnormality in a group of dogs with a median age of diagnosis of 16.1 months, being mainly bilateral in presentation 61 . Negishi et al also reported a case of optic nerve hypoplasia in a 6‐month‐old Beagle 62 …”
Section: Discussionmentioning
confidence: 86%
“…3 In a naturally occurring animal model of canine ONH, histologic studies suggested that although NFL and retinal ganglion cell layer thickness were hypoplastic, the outer retinal layers were preserved. 4 Macular hypoplasia has also been reported in other optic neuropathies such as the morning glory disc anomaly, 5 as well as in cases of acquired optic neuropathy associated with non-arteritic ischemic optic neuropathy, optic nerve head drusen, systemic lupus erythematosus, and pseudotumor cerebri. 6 In these optic neuropathies, cone photoreceptors displayed structural changes in the presence of permanent damage to the overlying inner retina layers (retinal ganglion cell-NFL-inner plexiform).…”
Section: Discussionmentioning
confidence: 95%
“…Localized retinal atrophy of the nerve fiber layer and the inner nuclear layer to retinal atrophy in all layers was observed in the retina. In cases of humans and dogs showing hypoplasia of the optic nerve, a decrease in the retinal ganglion cell layer and a thinning of the nerve fiber layer have been observed [14][15][16] . Therefore, this characteristic retinal thinning was probably attributable to optic nerve hypoplasia.…”
mentioning
confidence: 98%